Comparative Analysis of the RAB for the Kampi Sunter Hotel Development Project Structural Work Package between AHSP 2024 and AHSP 2025 - Afif Budi Santoso; Ervina Yuliyanti (Asosiasi Dosen Muda Indonesia, 2025)
the dynamics of the building materials market and labor costs. Therefore, a constantly updated reference is needed to ensure accurate and efficient project cost estimates. One such reference is the Work Unit Price Analysis (AHSP) which is released by the government periodically. This study aims to analyze and compare the Cost Budget Plan (RAB) value for structural work on the Kampi Sunter Hotel construction project based on the Work Unit Price Analysis (AHSP) versions 2024 and 2025. The method used is a quantitative approach through cost estimation calculations using both versions of the AHSP. The results show that the total cost of structural work based on the 2024 AHSP is Rp15,384,577,550, while based on the 2025 AHSP it is Rp13,830,592,539. There is a difference of Rp1,553,985,011 or a decrease of approximately 10.1% in the 2025 AHSP. This decrease is caused by changes in the unit price of materials, one of which is the price of Ready Mix Concrete K300 which decreased from Rp1,048,722.00 (2024) to Rp931,683.00 (2025). Therefore, it is important for project planners to always update the AHSP reference used to match the applicable year to be more relevant.